WEAK AND STRONG CONVERGENCE OF A KERNEL-TYPE ESTIMATOR FOR THE INTENSITY OF A PERIODIC POISSON PROCESSS - MANGKU, I W. (MILANG Journal of Mathematics and Its Applications, 2006)
In this paper we survey some results on weak and strong convergence of kernel type estimators for the intensity of a periodic Poisson process. We consider the situation when the period is known in order to be able to present simple proofs of the results. For the more general results, which includes the case when the period is unknown, we refer to [15], [16].1991 Mathematics Subject Classiﬁcation: 60G55, 62G05, 62G20.